Meningkatkan Aktivitas Belajar, Keterampilan Berpikir Kritis, Dan Hasil Belajar Siswa Pada Muatan PPKN Dengan Menggunakan Model Enggrang Di Kelas V SDN Barambai Kolam Kiri 5 - Elli Arliati Effendi; Ari Hidayat (CV. ITTC INDONESIA, 2024)
The problems that exist in this study are the low activity, critical thinking skills and student learning outcomes. This is because the teaching and learning process still applies teacher centered learning, and students have difficulty understanding the material on the socio-cultural diversity of society in Indonesia on Civics subjects. The solution to solving this problem is to use the ENGGRANG learning model which is a combination of the Problem Based Learning, Numbered Head Together, and Talking Stick models. The purpose of this research is to increase educator activity, student activity, critical thinking skills and student learning outcomes. This study applied Classroom Action Research (PTK) which was carried out in 4 meetings. The perpetrators of this study were fifth grade students at SDN Barambai Kolam Kiri 5, Barambai District, Barito Kuala Regency, with a total of 22 students consisting of 16 male students and 6 female students, in semester 2 of the 2022/2023 academic year. This research was conducted by applying a qualitative and quantitative approach. The data collected is qualitative data obtained through observing the activities of educators, participant activities and critical thinking skills then using quantitative data for student learning outcomes obtained through individual and group evaluations. The results of this study indicate that the teacher's activity at meeting 1 obtained a score of 17, increasing at each meeting until it reached a score of 23 with the